2005
DOI: 10.1259/dmfr/59267138
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondritis dissecans of the temporomandibular joint

Abstract: A case is reported of a 43-year-old female patient presenting bilateral osteochondritis dissecans (OCD) of the temporomandibular joint (TMJ), in different stages for each side, associated with avascular necrosis (AVN) of the right condyle. Additionally observed was anterior disk displacement without reduction for both sides. We have proposed an adaptation of the previous classification of OCD for cases affecting the TMJ. We have also stressed the fundamental role of panoramic radiography on the diagnosis of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 9 publications
0
10
0
1
Order By: Relevance
“…These alterations are considered to be radiological signs of osteoarthritis (OA) and have been demonstrated in painful TMJs 1,7,8,22 . Osteochondritis dissecans is frequently found in association with avascular necrosis 2,31 , and thus they have been considered similar conditions that may represent a spectrum of the same pathophysiology (bone necrosis) 34 .…”
mentioning
confidence: 99%
“…These alterations are considered to be radiological signs of osteoarthritis (OA) and have been demonstrated in painful TMJs 1,7,8,22 . Osteochondritis dissecans is frequently found in association with avascular necrosis 2,31 , and thus they have been considered similar conditions that may represent a spectrum of the same pathophysiology (bone necrosis) 34 .…”
mentioning
confidence: 99%
“…29 Although it is difficult to assert the cause of OCD, possible factors may be focal trauma, abnormal ossification, avascular necrosis, genetic factors or combination of these factors. 28,30 Importantly, in humans it can be symptomatic causing pain, swelling and limited jaw movement or it can be entirely asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Schellhas et al (1989:551) also suggested that mandibular condyle OCD is relatively common and often associated with internal derangement of the TMJ. While OCD in general can occur in both adolescents and adults, it tends to be more common in males (Campos et al, 2005). When considering OCD as a candidate for the condylar concavities described in this study, it is important to note Bohndorf (1998:106): '[a]s a general rule, most OCD lesions occur at the weight-bearing convex cartilage'.…”
Section: Osteochondritis Dissecansmentioning
confidence: 93%
“…OCD is characterised by necrosis of the subchondral bone which can become detached and form a loose body within the joint space (Campos et al, 2005). While there is a rich literature on the aetiology of OCD, Bohndorf (1998:105) summarised the consensus view implicating joint overuse and/or repetitive microtrauma as particularly important.…”
Section: Osteochondritis Dissecansmentioning
confidence: 99%